Electron paramagnetic resonance microscopy using spins in diamond under ambient conditions - David A. Simpson (Nature Portfolio, 2017)
Electron paramagnetic resonance spectroscopy has important scientific and medical uses but improving the resolution of conventional methods requires cryogenic, vacuum environments. Simpson et al. show nitrogen vacancy centres can be used for sub-micronmetre imaging with improved sensitivity in ambient conditions.